2018
DOI: 10.1016/j.nedt.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Malaysian Nurses' perspectives of intercultural teaching in transnational higher education learning environments

Abstract: There is a need for TNHE 'flying faculty' to internationalise the theoretical knowledge to reduce cultural incongruities and dissimilarities. Cultural immersion will stimulate intercultural views and knowledge to equip nurses for promotional and/or global opportunities whilst enabling the 'flying faculty' to create new learning environments. The research provides insights to inform TNHE provider institutions to improve teaching and learning to enable nurses to make the theory-practice connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In fact, the need for academic and cultural support of diverse students is widely acknowledged [54]. According to Arunasalam and Burton [57] and Mackay et al [54], diverse students face three main challenges: difficulties with language if the local language is not their mother tongue, differences in education style, and social integration and connectedness. Nursing educators have an essential role to play in helping to create a positive learning environment for culturally diverse learners [58].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the need for academic and cultural support of diverse students is widely acknowledged [54]. According to Arunasalam and Burton [57] and Mackay et al [54], diverse students face three main challenges: difficulties with language if the local language is not their mother tongue, differences in education style, and social integration and connectedness. Nursing educators have an essential role to play in helping to create a positive learning environment for culturally diverse learners [58].…”
Section: Discussionmentioning
confidence: 99%
“…Support is an essential component of the stamina to complete BN study (Kalman et al, 2009;Osterman et al, 2009;Winokur et al, 2016;Arunasalam & Burton, 2018). RNs in this study were sustained through the ups and downs of the program first by their families who provided encouragement and practical support such as child minding.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Maintaining work-life balance is a struggle. Strains occur when RNs find themselves unprepared for the program workload, with outdated academic skills, unfamiliar with technology, with fears of failing (Duffy et al, 2014;Kenny, Kidd, Nankerris, & Connell, 2011;Megginson, 2008) and experiencing cultural dissonance with the higher education institution (Arunasalam & Burton, 2018). Managing time and taking time away from family and friends to study are difficult (Kalman et al, 2009;Megginson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, domestic students have mixed with international students in a classroom setting, where among others, they reported that they bene ted in developing awareness, connecting, and sharing cultural knowledge (O'Brien, Tuohy et al 2019). In other institutions, academic mobility involves having faculty from abroad to teach students in their home country, which has both positive and negative impacts on both students and faculty (Arunasalam and Burton, 2018;Huang et al, 2019). Some institutions embrace international exchange programs for students and faculty, which in uences their literature and functional value in terms of having a contextual value of studying abroad (Gallarza et al, 2017) and promoting cultural self-awareness and professional development (Hepple et al, 2017).…”
Section: Introductionmentioning
confidence: 99%